Young people’s perspective on the influence of alcohol, tobacco, vaping and fast food industries - Dickenson, Joseph; Devlin, Sean (Future healthcare journal, 2025)
As young people, alcohol, tobacco, vapes and fast food are everywhere in our lives. They are commonplace at social events, in our media, and in adverts; explained away as part of growing up. Many young people are unaware of the health risks of these substances, partly due to the success of industry marketing. For example, most people are aware of the risks to their livers from drinking alcohol, but far fewer of us realise the small scale of consumption required. The rise of vaping and fast food in particular has been accelerated by their low cost and widespread availability. As teenagers, most of us have limited spending power – our income comes from Saturday jobs or a handful of hours of shift work, so processed foods are the easiest choice. Vapes are easily available on most high streets, and young people often pass shops that sell them on their way to school. Society’s casual attitude towards these promotes more consumption and obscures the risks. Our social media feeds influence us all, in a myriad of ways, ranging from athletes promoting an ideal body image, to companies sponsoring adverts for their products, to influencers casually showing alcohol, smoking and vaping as part of their regular lives. We explore solutions such as tighter regulations on packaging; clearer labelling of the risks of substances can help young people to make healthier, more informed decisions. We propose that vapes be subject to the same regulations as tobacco on storage, and mandating drab packaging; moving away from the bright, colourful designs that seem designed to target children specifically. Increasing the duty paid on these products could be beneficial, but it risks pushing consumers to potentially more risky alternatives, and further widens the socio-economic divide between rich and poor. We also suggest that teaching children to think critically from a young age will enable them to make better decisions about their health, as well as many other aspects of their lives.